2018
DOI: 10.1016/j.ceb.2018.05.006
|View full text |Cite
|
Sign up to set email alerts
|

Bench to bedside: Current advances in regenerative medicine

Abstract: Regenerative medicine is a diverse and rapidly evolving field, employing core expertise from biologists, engineers, and clinicians. Recently the field has made significant progress towards regenerating or replacing tissues lost to age, disease or injury. Current strategies include transplantation of adult or pluripotent stem cells to replace tissue or support tissue healing. Promising approaches for the future of regenerative medicine include stimulating endogenous stem cells for in situ repair, transplantatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
4
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(4 citation statements)
references
References 57 publications
0
4
0
Order By: Relevance
“…Stem cell and regenerative medicine research is making steady progress from the bench to the bedside [1]. Along with this growth and progress, specific challenges have emerged.…”
mentioning
confidence: 99%
“…Stem cell and regenerative medicine research is making steady progress from the bench to the bedside [1]. Along with this growth and progress, specific challenges have emerged.…”
mentioning
confidence: 99%
“…What is more, although stem cell delivery with DAF‐G might show a better result in the repair of AF defect, cell‐based therapy is not a very convenient and highly operable way to induce regeneration. An alternative and attractive strategy for regenerative medicine is to target endogenous repair mechanisms in resident cell populations to induce in situ regeneration (Clarke et al, ). The outcomes suggested that the decellularized matrix provided hospitable cell niches and the biochemical cues for resident cells' migration and growth (D'Este, Eglin, & Alini, ).…”
Section: Discussionmentioning
confidence: 99%
“…For example, ruptures require in most cases a surgical intervention, while other conditions may benefit from conservative therapies in order to control symptoms and possibly halt the degenerative process [28, 58]. In the scenario of non‐surgical approaches, regenerative medicine aims to promote and sustain tissue repair by exploitation of the self‐healing ability of the body [6, 25]. Regenerative medicine comprises a number of approaches, including the application of orthobiologics, i.e.…”
Section: Introductionmentioning
confidence: 99%